Kompetensi Petani dalam Usahatani Lada di Desa Kosebo Kecamatan Angata Kabupaten Konawe Selatan - Israwan Israwan; Weka Widayati; Budiyanto Budiyanto; La Ode Geo; Awaluddin Hamzah (Jurnal Sosio Agribisnis, 2019)
This study aims to describe the competence of farmers in pepper farming. The research location was in the Kosebo Village, Angata Subdistrict, Konawe Selatan District that was chosen purposively, with the consideration that the village was the center of pepper production in Konawe Selatan Regency. The study population is all pepper farmers, amounting to 300 people. The sampling technique is done by simple random sampling. Determination of the number of samples using the Slovin formula to obtain a sample of 75 pepper farmers. The research variables consisted of 2 (two) competencies, namely the level of knowledge and skills of farmers in terms of aspects of cultivation techniques, starting from land preparation/planting hole, climbing pole planting, seed selection/ planting, plant maintenance (pest and disease control) to harvesting. Data analysis was performed descriptively qualitative. The results showed that the level of knowledge and skills of farmers who were well understood and mastered related to pepper cultivation, namely aspects of land preparation/planting hole, climbing pole planting, selection of seeds, planting and harvesting, while aspects of crop maintenance specifically control of stem rot rot were not yet understood and well controlled by farmers.Keywords: competence; farmers; pepper farming